Public expenditures and economic growth: an empirical examination for Greece by cointegration analysis - Δριτσάκης, Νικόλαος; Βαζακίδης, Αθανάσιος (SPOUDAI Journal of Economics and Business, 2003)
This paper investigates the relationship between the public expenditures and the economic growth using annual data covering the period from 1960 to 2001 for Greece. The purpose of this paper is to test the long-run relationship between the public expenditures and the economic growth using the cointegration analysis as suggested by Johansen and Juselious. Then an error correction model is applied to estimate the short-run and the long-run relationships of the model's variables and the prediction of public expenditures as well. The results of our analysis show that there is a long-run relationship between the public expenditures and the economic growth for Greece. JEL Classification: A10, C22